The effect different of temperature on growth and survival rate of Kryptopterus lais - Gunawan, Hariadi; Tang, Usman Muhammad; Mulyadi, Mulyadi (Jurnal Perikanan dan Kelautan, 2019)
This study aims to determine the effect different of temperature on growth and survival rateof Kryptopterus lais.This research was conducted at the Aquaculture Laboratory, Faculty of Fisheries and Marine Science University of Riau, on march to may, 2018. The trial fish used in this research was Kryptopterus lais.The experimental design used was completely randomized design with 5 treatments and 4 replicateswith four treatment temperature25oC, 27oC, 29oC, 31oC, and 33oC. Analysis was performed on specific growth rate weigh, ansolute growth, specific growth rate and survival rate. The results showed that the specific growth rate weigh (34,22 ± 0,22e), ansolute growth (5,75 ± 0,29c), specific growth rate(7,12 ± 0,03d) and survival rate (92,50 ± 2,89b) is highest in treatment temperature29oC.Temperature effect in treatment of 29oC had significant effect on specific growth rate weigh, ansolute growth, specific growth rate and survival rate(p < 0.05).  it can be concluded that the optimum temperatureimproved specific growth rate weigh, ansolute growth, specific growth rate and survival rate.